Synovitis in rheumatoid arthritis detected by grey scale ultrasound predicts the development of erosions over the next three years. (19th October 2019) - Möller, Burkhard; Aletaha, Daniel; Andor, Michael; Atkinson, Andrew; Aubry-Rozier, Bérengère; Brulhart, Laure; Dan, Diana; Finckh, Axel; Grobéty, Véronique; Mandl, Peter; Micheroli, Raphael; Nissen, Michael John; et al.
Abstract: Objectives: To evaluate grey scale US (GSUS) and power Doppler US synovitis (PDUS), separately or in combination (CombUS), to predict joint damage progression in RA. Methods: In this cohort study nested in the Swiss RA register, all patients with sequential hand radiographs at their first US assessment were included. We analysed the summations of semi-quantitative GSUS, PDUS and CombUS assessments of both wrists and 16 finger joints (maximum 54 points) at their upper limit of normal, their 50th, 75th or 87.5th percentiles for the progression of joint damage (ΔXray). We adjusted for clinical disease activity measures at baseline, the use of biological DMARDs and other confounders. Results: After a median of 35 months, 69 of 250 patients with CombUS (28%), 73 of 259 patients with PDUS (28%) and 75 of 287 patients with available GSUS data (26%) demonstrated joint damage progression. PDUS beyond upper limit of normal (1/54), GSUS and CombUS each at their 50th (9/54 and 10/54) and their 75th percentiles (14/54 and 15/54) were significantly associated with ΔXray in crude and adjusted models. In subgroup analyses, GSUS beyond 14/54 and CombUS higher than 15/54 remained significantly associated with ΔXray in patients on biological DMARDs, while clinical disease activity measures had no significant prognostic power in this subgroup. Conclusion: Higher levels of GSUS and CombUS are associated with the development of erosions. GSUS appears to be an essential component of synovitis assessment and an independent predictor of joint damage progression in patients on biological DMARDs.